Buzzing during biosonar-based interception of prey in the delphinids Tursiops truncatus and Pseudorca crassidens - Wisniewska, Danuta M.; Johnson, Mark; Nachtigall, Paul E.; Madsen, Peter T. (Journal of Experimental Biology, 2014)
Echolocating bats and toothed whales probe their environment with ultrasonic sound pulses, using returning echoes to navigate and find prey in a process that appears to have resulted from a remarkable convergence of the two taxa. Here, we report the first detailed quantification of echolocation behaviour during prey capture in the most studied delphinid species, a false killer whale and a bottlenose dolphin. Using acoustic DTAGs, we demonstrate that just prior to prey interception these delphinids change their acoustic gaze dramatically by reducing inter-click intervals and output >10-fold in a high repetition rate, low output buzz. Buzz click rates of 250-500 Hz for large but agile animals suggest that sampling rates during capture are scaled with the whale's manoeuvrability. These observations support the growing notion that fast sonar sampling accompanied by a low output level is critical for high rate feedback to inform motor patterns during prey interception in all echolocating toothed whales.